2016
DOI: 10.1080/15384047.2016.1139248
|View full text |Cite
|
Sign up to set email alerts
|

An anti-HER2 antibody conjugated with monomethyl auristatin E is highly effective in HER2-positive human gastric cancer

Abstract: Antibody-drug conjugate (ADC) is a novel class of therapeutics for cancer target therapy. This study assessed antitumor activity of ADC with an antimitotic agent, monomethyl auristatin E (MMAE) and a humanized monoclonal anti-HER2 antibody, hertuzumab, in gastric cancer. The efficacy of hertuzumab-MC-Val-Cit-PAB-MMAE (hertuzumab-vcMMAE) on human epidermal growth factor receptor 2 (HER2) positive human gastric cancer cells, NCI-N87, was evaluated in vitro and in vivo. The cytotoxicity of hertuzumab was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…Our results demonstrated that the chemistry used for ADC preparation did not diminish rituximab-specific binding to cell surface CD20. In agreement of our study, similar results were also found in previous studies [27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 94%
“…Our results demonstrated that the chemistry used for ADC preparation did not diminish rituximab-specific binding to cell surface CD20. In agreement of our study, similar results were also found in previous studies [27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 94%
“…MMAE is a highly potent cytotoxin that can block microtubulin polymerization but has never been tested in NETs. (40)(41)(42)(43) In this study, the IC50 values of MMAE, ADC from our mAb, and ADC from the commercial mAb were 2.00, 4.27, and 5.62 nM, respectively (Fig. 5D).…”
Section: In Vitro Anti-cancer Toxicity Of Adcmentioning
confidence: 49%
“…Fortunately, hG7-BM3 exhibited all of these properties. Therefore, we generated an hG7-BM3-VcMMAE conjugate, which increased the anti-tumor potency of hG7-BM3 and broadened the therapeutic window of MMAE [ 35 , 36 ]. The observable decrease in tumor volume in the in vivo assay indicated that the anti-tumor efficacy of hG7-BM3-VcMMAE was dramatically improved in comparison with either parental hG7-BM3 or native MMAE alone.…”
Section: Discussionmentioning
confidence: 99%